Long‐term selection for litter size in swine results in shifts in allelic frequency in regions involved in reproductive processes. (26th May 2016) - Trenhaile, M. D.; Petersen, J. L.; Kachman, S. D.; Johnson, R. K.; Ciobanu, D. C.
Summary: High‐density genotype data were analyzed in three lines of swine that express substantial variation in sow fertility to uncover regions of the genome potentially influenced during selection for litter size traits. The experimental lines examined include the Nebraska Index Line (NIL), which has been subjected to long‐term selection for litter size; a control line derived from the same population that founded NIL; and a commercial Duroc × Hampshire (D × H) population, in which no selection for litter size was practiced. Regions of the genome potentially affected by selection for litter size traits in NIL were determined by multiple lines of evidence, including altered allelic frequency compared to the other lines, loss of heterozygosity and relative extended haplotype homozygosity. Additionally, a genome‐wide association study for litter size traits was conducted in a population based on NIL and commercial maternal line genetics. Several genomic regions identified as putative signatures of selection overlapped with QTL for litter size traits. One of these regions, located on SSC2 (13–14 Mb), includes the candidate gene P2X3R, which plays a role in implantation and sustained release of hormones associated with reproductive processes. Sequencing identified synonymous SNPs in P2X3R that are fixed in NIL but polymorphic with nearly equal frequencies in the D × H line, indicating a potential role of P2X3R in sow fertility. These results suggest that data derived from these lines can help to uncover and understand a portion of the genetic variance associated with fertility traits in swine.